Functional Evolution of the Kernavė Hillforts in the Iron Age: New Intepretations of Old Data - Vengalis, Rokas; Vėlius, Gintautas (Archaeologia Lituana, 2019)
This article explores the finds and post-excavation reports of earlier archaeological investigations in the five Kernavė hillforts. The detailed analysis of the assembled finds, discovered features and structures made it possible to revise and improve the prieviously suggested evolution model for the Kernavė hillforts. It reveals the evolution of the hillforts to have been much more complicated and that, over time, their function has changed rather significantly more than once. The finds recovered during earlier excavations were not classified into primary, secondary and de facto refuse. New examination of refuse – in this case, of pottery sherds, allowed for identification of single events, short-term activities and long-term settlement on the hillforts as well as distinct functional areas. The authors discuss whether the term “hillfortˮ is appropriate for use in scientific historiography. The issue of actual contemporaneity of the hilfforts in hilffort complexes is also raised.
Keywords: hillfort function; activity areas; Kernavė; pottery; fortifications